REVIEW OF ISLAMIC FINANCIAL MANAGEMENT ON THE MANAGEMENT OF RESOURCES OF FUNDS IN BMT AL-HASAN MITRA UMMAT: : Study of Effectiveness, Efficiency and Accountability - Zamroni Alpian Muhtarom (Al-Qardhu, 2023)
This paper discusses the review of Islamic financial management on the management of sources of funds at BMT Al-Hasan Mitra Ummat. In this article, the authors examine three scopes, namely effectiveness, efficiency and accountability in the management of financial resources. To obtain data regarding the main theme, the authors use field research methods and rigorous and mathematical validation methods. After going through lengthy research, the authors found that from 2018-2020 the results of the service operational cost ratio show very efficient and efficient. Then the fixed asset ratio and service efficiency ratio both show less efficient criteria. The effectiveness of the working capital turnover ratio at BMT Al-hasan Mitra Ummat from 2018-2019 the ratio is ≥5.3 with a value of 100 and in 2020 the ratio is 2.5 to <3.5 with a value of 75 This indicates that the turnover of working capital is very effective and effective. Meanwhile, in terms of Return On Assets (ROA) of BMT Al-hasan Mitra Ummat from 2018-2020. Where in 2018 the total Return On Assets (ROA) was 20.31% at the ROA level ≥ 10% with an assessment of 100 and very effective. In 2019 the Return On Assets (ROA) of 2.1% is at the ROA level of 1% to <3% with an assessment of 25 and less effective criteria. In 2020 the Return On Assets (ROA) of -1.7% is at the ROA level ≤ 1% with a rating of 0 and the criteria are not effective. In the Accountability of the BMT Al-hasan Mitra Ummat cooperative in presenting financial statements it has not met the listed Financial Accounting Standards for Entities Without Public Accountability (SAKETAP).